Electrodynamics of Radiating Charges - Øyvind Grøn (Advances in Mathematical Physics)
The theory of electrodynamics of radiating charges is reviewed with special emphasis on the role of the Schott energy for the conservation of energy for a charge and its electromagnetic field. It is made clear that the existence of radiation from a charge is not invariant against a transformation between two reference frames that has an accelerated motion relative to each other. The questions whether the existence of radiation from a uniformly accelerated charge with vanishing radiation reaction force is in conflict with the principle of equivalence and whether a freely falling charge radiates are reviewed. It is shown that the resolution of an electromagnetic “perpetuum mobile paradox” associated with a charge moving geodetically along a circular path in the Schwarzschild spacetime requires the so-called tail terms in the equation of motion of a charged particle.